The Construction of Borders in Post 9/11 Muslim Pakistani Fiction - Noura Shafie; Samar H. Aljahdali (International Journal of English Language and Translation Studies, 2020)
The 9/11 events have marked a new shift in border studies. Pakistani writers have engaged with (mis)representations of Muslims, giving voice to silenced immigrants who narrate their experience in the U.S before and after the attacks. This paper investigates the representations of abstract and concrete borders in post 9/11 Muslim Pakistani fiction, with particular focus on Bapsi Sidhawa’s An American Brat (1993), Mohsin Hamid’s the Reluctant Fundamentalist (2007) and H. M Naqvi’s Home Boy (2009). While based on postcolonial theoretical framing, the study draws on K. Alrasheed’s (2015) recent conceptualization of neo-Orientalism and D. Newman’s (2006, 2015, 2017) theorization of borders in the wake of the 9/11 events. The study engages with how the 9/11 events have redefined borders, and invigorated a securitzation discourse that embraces the separation and exclusion of ethnic minorities. The selected novels, while presenting the unheard and counter narratives of the Muslim subaltern, have shown how the tightening of borders, both concrete and cultural, has limited the mobility of Muslim immigrants in the US and relegated them to marginalized enclaves.